2008
DOI: 10.1007/s00018-008-8305-x
|View full text |Cite
|
Sign up to set email alerts
|

Proliferating cell nuclear antigen: a proteomics view

Abstract: Proliferating cell nuclear antigen (PCNA), a cell cycle marker protein, is well known as a DNA sliding clamp for DNA polymerase delta and as an essential component for eukaryotic chromosomal DNA replication and repair. Due to its mobility inside nuclei, PCNA is dynamically presented in a soluble or chromatin-associated form. The heterogeneity and specific modifications of PCNA may reflect its multiple functions and the presence of many binding partners in the cell. The recent proteomics approaches applied to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
171
1
9

Year Published

2010
2010
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 203 publications
(189 citation statements)
references
References 194 publications
8
171
1
9
Order By: Relevance
“…29,30 Similar expression patterns have been reported for PCNA homologs in yeast. 31 and in the related kinetoplastid parasite, Leishmania donovani.…”
Section: Resultssupporting
confidence: 74%
“…29,30 Similar expression patterns have been reported for PCNA homologs in yeast. 31 and in the related kinetoplastid parasite, Leishmania donovani.…”
Section: Resultssupporting
confidence: 74%
“…1A vs C). Annexin A2 (ANXA2), elongation factor 1 (EF1A), and glyceraldehyde-3-phosphate dehydrogenase (G3P) were shown previously to interact with PCNA [28][29][30][31][32], and the rest is reported here for the first time. The levels of three gene products involved in protein synthesis (RSSA, MDHM, and EF1A) were substantially higher in cancer than HMEC cells ( Fig.…”
Section: Identification Of Pcna-binding Proteins In Normal and Cancermentioning
confidence: 68%
“…Much knowledge about PCNA function was gained by structure/function studies that identified a PCNA hydrophobic pocket as the docking site for most PIP box motif-carrying proteins (41). Based on the structural similarity between the 9-1-1 complex and PCNA, we hypothesized that the outer surface of HUS1 would mediate physical interactions with downstream effectors.…”
Section: Discussionmentioning
confidence: 99%